104k views
5 votes
If (x) = 3^x + 10x and g(x) = 4x - 2, find (1-g) (x).

1 Answer

5 votes

Answer:We are given:

f(x) = 3x + 10x

g(x) = 4x - 2

(f-g)(x) is saying we want to take f(x) and subtract g(x).

Symbolically, (f-g)(x) = f(x) - g(x) = 3x + 10x - (4x - 2) = 3x + 10x - 4x + 2 = 3x + 6x + 2

Thus, (f-g)(x) = 3x + 6x + 2

Step-by-step explanation: The main points of the problem is to understand the notation of (f-g)(x) and to remember to distribute a negative throughout g(x) due to the subtraction.

User Noby
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.